Development of a spatial-dynamical model of the structure of toxic cyanobacteria clusters for biosecurity purposes - Vysotska, O.; Georgiyants, M.; Nosov, K.; Balym, Yu.; Pecherska, A.; Porvan, A.; Pavlov, S.; Shekhovtsova, V.; Klochko, T.; Solodovnikov, A. (My University, 2018)
We have devised a spatialdynamic model that describes the structure of clusters of toxic cyanobacteria over large water areas. The application of the constructed model has been demonstrated in order to identify the structure of a cluster in digital photographs. The character of bioproductive processes that define the risk of accumulation of toxic microorganisms is determined by a series of parameters that can be measured remotely using aerospace methods (taking photographs). The proposed model, based on a digital image, makes it possible to restore the spatialdynamic pattern of clusters by determining the state of bioproductive processes in different parts of the cluster. Information about such states is of great importance in order to optimize measures for eliminating the threat of toxicity.
Keywords: spatialdynamical model; cyanobacteria; bioproductive processes; colorimetric parameters; biosecurity